2021
DOI: 10.1037/pha0000386
|View full text |Cite
|
Sign up to set email alerts
|

Predicting college student prescription stimulant misuse: An analysis from ecological momentary assessment.

Abstract: Prescription stimulant misuse (PSM) is common in young adult college students, at over 10% in the past year, and it is associated with other substance use and risk behaviors. Research focused on the real-time drivers of PSM is absent, impeding prevention and intervention. This research aimed to fill that gap by examining the relationships between affect, global stress, or academic stress and PSM via ecological momentary assessment (EMA); we also investigated baseline predictors of PSM frequency during the 21-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 55 publications
3
8
0
Order By: Relevance
“…Theory suggests that problematic substance use occurs as a means to reduce negative mood (Khantzian, 1997), which provides a simple and reasonable explanation for the documented within- and between-person links between negative mood and prescription misuse behaviors. Interestingly, the unexpected finding of elevated momentary positive mood predicting misuse does align with recent evidence from a different college-based sample: Schepis et al (2020) collected participants’ reported motives for prescription stimulant misuse soon after the occurrence of the behavior in daily life. They found that positive mood reliably increased in the hours following misuse occurrence, and thus interpreted positivity enhancement —or the motivation to increase positive feelings—as a key driver of students’ prescription stimulant misuse in daily life (Schepis et al, 2020).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Theory suggests that problematic substance use occurs as a means to reduce negative mood (Khantzian, 1997), which provides a simple and reasonable explanation for the documented within- and between-person links between negative mood and prescription misuse behaviors. Interestingly, the unexpected finding of elevated momentary positive mood predicting misuse does align with recent evidence from a different college-based sample: Schepis et al (2020) collected participants’ reported motives for prescription stimulant misuse soon after the occurrence of the behavior in daily life. They found that positive mood reliably increased in the hours following misuse occurrence, and thus interpreted positivity enhancement —or the motivation to increase positive feelings—as a key driver of students’ prescription stimulant misuse in daily life (Schepis et al, 2020).…”
Section: Discussionsupporting
confidence: 76%
“…
The present study addressed calls for research to identify real-time predictors of prescription drug misuse (Schepis et al, 2020) by testing young adults' momentary reports of their negative mood and positive mood as predictors of event-level misuse in daily life. We implemented a 28-day ecological momentary assessment (EMA) procedure that collected individuals' mood and other contextual experiences in moments preceding prescription drug misuse.
…”
mentioning
confidence: 99%
“…Interestingly, recent research that collected college students' motivations for stimulant misuse soon after the behavior had occurred documented greater positive affect on days with the misuse. 50 Clearly, incorporating multiple domains of real-time triggers of prescription drug misuse is warranted in future research.…”
Section: Discussionmentioning
confidence: 99%
“…Such misuse is commonly documented via retrospective reports of behaviors over the past year (McCauley et al, 2011) or previous semester (Chinneck et al, 2018). Researchers (Nargiso et al, 2015;Schepis et al, 2020) have called for ecologically-based investigations of prescription drug misuse to identify its triggers in real-world environments to advance prevention and intervention efforts. Ecologically-based methods, such as ecological momentary assessment (EMA), offer advantages of reducing recall biases and -critically for research on misuse in which the clinical effect of the medications can reinforce expected outcomes-collecting contextual and psychological experiences prior to the occurrence of the behavior (Ferguson & Shiffman, 2011;Shiffman et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Ecologically-based methods, such as ecological momentary assessment (EMA), offer advantages of reducing recall biases and -critically for research on misuse in which the clinical effect of the medications can reinforce expected outcomes-collecting contextual and psychological experiences prior to the occurrence of the behavior (Ferguson & Shiffman, 2011;Shiffman et al, 2008). Recent studies assessing substance use behavior close to its occurrence Schepis et al, 2020) have been useful for identifying predictors of behavior, offering useful information for prevention and treatment efforts. EMA also allows assessment of the contextual setting of substance use behaviors.…”
Section: Introductionmentioning
confidence: 99%